EZPasar / Firdaus Haqimi Abdul Halim Chua … [et al.] - Abdul Halim Chua, Firdaus Haqimi; Wan Mohd Noor, Wan Noranida; Mohd Nurfikri, Nazatul Wahidah; Tukimin, Nor Aziha; Sazali, Norsharizatul Nasywa (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
People with disabilities, especially those who are visually impaired, frequently find it difficult to navigate traditional market and independently seek specific stalls. Their sense of inclusion is hampered by this lack of accessibility, which also restricts their capacity to participate in daily activities. This problem is addressed by the EZPasar application, which offers a user- friendly interface that enables users to identify desirable market stalls with just one click. By utilizing GPS technology and comprehensive stall information, EZPasar improves navigation by providing step-by-step guidance to users to their selected location. The main target audience for EZPasar is people with disabilities, particularly those who are visually impaired, giving them the ability to confidently and easily navigate markets. Furthermore, the application is accessible, welcoming all users including those without disabilities who are looking for a quick and easy way to get around crowded traditional market. In an effort to close the gap between the requirements of individuals with disabilities and typical market contexts, EZPasar places a high priority on inclusion and accessibility. The application fosters a more inclusive society by providing a customized solution to traverse marketplaces, hence promoting equal access to goods and services. By enabling visually impaired people to independently explore marketplaces, EZPasar promotes a sense of freedom and independence. EZPasar saves time and effort by streamlining the purchasing process for all consumers by offering exact directions to requested stalls. Looking ahead, EZPasar holds promising prospects for further development and impactful expansion. Although EZPasar was developed for use in traditional markets, it might be adapted for use in other environments, like shopping malls, airports, and hubs for public transportation. Increasing the application's scope can enhance its usefulness and make it more appealing to a larger audience.